A comparative evaluation of PDQ-Evidence - Marit Johansen; Gabriel Rada; Sarah Rosenbaum; Elizabeth Paulsen; Nkengafac Villyen Motaze; Newton Opiyo; Charles S. Wiysonge; Yunpeng Ding; Fidele K. Mukinda; Andrew D. Oxman (BMC, 2018)
Abstract Background A strategy for minimising the time and obstacles to accessing systematic reviews of health system evidence is to collect them in a freely available database and make them easy to find through a simple 'Google-style' search interface. PDQ-Evidence was developed in this way. The objective of this study was to compare PDQ-Evidence to six other databases, namely Cochrane Library, EVIPNet VHL, Google Scholar, Health Systems Evidence, PubMed and Trip. Methods We recruited healthcare policy-makers, managers and health researchers in low-, middle- and high-income countries. Participants selected one of six pre-determined questions. They searched for a systematic review that addressed the chosen question and one question of their own in PDQ-Evidence and in two of the other six databases which they would normally have searched. We randomly allocated participants to search PDQ-Evidence first or to search the two other databases first. The primary outcomes were whether a systematic review was found and the time taken to find it. Secondary outcomes were perceived ease of use and perceived time spent searching. We asked open-ended questions about PDQ-Evidence, including likes, dislikes, challenges and suggestions for improvements. Results A total of 89 people from 21 countries completed the study; 83 were included in the primary analyses and 6 were excluded because of data errors that could not be corrected. Most participants chose PubMed and Cochrane Library as the other two databases. Participants were more likely to find a systematic review using PDQ-Evidence than using Cochrane Library or PubMed for the pre-defined questions. For their own questions, this difference was not found. Overall, it took slightly less time to find a systematic review using PDQ-Evidence. Participants perceived that it took less time, and most participants perceived PDQ-Evidence to be slightly easier to use than the two other databases. However, there were conflicting views about the design of PDQ-Evidence. Conclusions PDQ-Evidence is at least as efficient as other databases for finding health system evidence. However, using PDQ-Evidence is not intuitive for some people. Trial registration The trial was prospectively registered in the ISRCTN registry 17 April 2015. Registration number: ISRCTN12742235.